G-quadruplex-proximity protein labeling based on peroxidase activity. Issue 78 (1st September 2020) - Masuzawa, Tatsuki; Sato, Shinichi; Niwa, Tatsuya; Taguchi, Hideki; Nakamura, Hiroyuki; Oyoshi, Takanori
Abstract : G-quadruplex-proximity protein labeling was performed using a hemin-parallel G-quadruplex (G4) complex. A tyrosine labeling reaction was accelerated in close proximity to the hemin with enhanced peroxidase activity by binding to parallel G4. Abstract : Peroxidase-proximity protein labeling was performed using a hemin-parallel G-quadruplex (G4) complex. A tyrosine labeling reaction using an N -methyl luminol derivative was accelerated in close proximity to the hemin with enhanced peroxidase activity by binding to parallel G4. The TERRA–hemin complex activated the labeling of many RNA-binding proteins, including heterogeneous nuclear ribonucleoproteins, in a HeLa cell lysate.